Ti-based flux-cored wire suitable for titanium alloy sheet laser brazing, preparation method and application
By using Ti-based medicinal cord wire materials with elements such as Zr, Cu, Ni, Cr, etc. for laser brazing of titanium alloy thin plates, the problems of low bond strength and welding defects of existing brazing joints are solved, and high-strength and excellent corrosion-resistant welding effects are achieved.
Patent Information
- Application Number
- CN202411948017.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-27
AI Technical Summary
The existing Ti-based solder is prone to problems of low joint bonding strength and welding defects in laser brazing of titanium alloy thin plates.
Ti-based medicinal cord wire materials including Zr, Cu, Ni, Cr and other elements are used to form a structure of a medicinal core and a skin through specific preparation and preparation methods, and are used for laser brazing of titanium alloy thin plates.
It realizes brazed joints with good welding properties and no welding defects, has high strength and excellent corrosion resistance, and is suitable for welding structures that withstand certain loads.
Smart Images

Figure CN119635070A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of brazing materials, and in particular relates to a Ti-based flux-cored wire suitable for laser brazing of titanium alloy thin plates and a preparation method thereof, and also relates to the application of the Ti-based flux-cored wire. Background Art
[0002] Due to the excellent strength, corrosion resistance and light weight of titanium alloys, their plates are often used in the manufacturing of equipment such as aerospace, medical equipment, chemical equipment, and high-end sports equipment.
[0003] Due to the limitations of their own structure and material properties, some titanium alloy thin plate components are difficult to manufacture as a whole and can only be manufactured by segmented processing and then assembly, such as aircraft fuselage skins, chemical reactor walls and other complex equipment. To ensure that these components will not deform or loosen during use, a permanent connection method such as welding must be used. At present, the welding methods suitable for titanium alloy thin plates include metal arc gas welding (MAG welding), tungsten inert gas welding (TIG welding), plasma welding, etc. Compared with the aforementioned welding methods, as a newer welding method, laser brazing of titanium alloy thin plates has the following advantages: (1) The tendency of intermetallic compounds to form is greatly reduced (2) It is easy to control the heat and welding thermal cycle. (3) The melting position can be precisely controlled.
[0004] Traditional Ti-based brazing fillers have the advantages of high joint strength and excellent corrosion resistance in laser brazing of titanium alloy thin plates. However, they often face problems such as low joint strength, easy welding defects, and high production costs. Summary of the invention
[0005] The first object of the present invention is to provide a Ti-based flux-cored wire suitable for laser brazing of titanium alloy thin plates, which solves the problem that the existing Ti-based flux-cored wire brazing material is prone to low joint strength and welding defects after welding.
[0006] The second object of the present invention is to provide a method for preparing a Ti-based flux-cored wire suitable for laser brazing of titanium alloy thin plates.
[0007] The third object of the present invention is to provide applications of Ti-based cored wires.
[0008] The first technical solution adopted by the present invention is: a Ti-based flux-cored wire suitable for laser brazing of titanium alloy thin plates, including a flux core and an outer skin, wherein the flux core includes Zr: 20%~45%, Cu: 20%, Ni: 20%, Cr: 15%~40% in atomic percentage, and the total of the above atomic percentages is 100%; the weld skin is a TA1 strip, and the weld skin includes, in mass percentage, H: 0.015%, O: 0.18%, N: 0.05%, C: 0.26%, Fe: 0.2%, and the balance is Ti.
[0009] The functions of each element of Ti-based flux-cored wire solder are: Ti: It can provide excellent high temperature resistance and chemical stability, and at the same time help to form a good metallurgical bond with the TC4 titanium alloy matrix, thereby enhancing the strength and corrosion resistance of the brazed joint.
[0010] Zr: Zr is a neutral element in Ti alloys. It can be infinitely dissolved in each other (it can form a continuous solid solution with α-Ti and β-Ti), and has a solid solution strengthening effect on Ti, especially the high temperature strengthening effect. It will not form brittle intermetallic compounds with Ti. Zr can also improve the creep resistance of TC4 and improve the strength of the alloy without significantly reducing the plasticity of titanium alloy.
[0011] Cu / Ni: Cu and Ni are both β-Ti stabilizers, with similar atomic size and structure, and can form an infinite solid solution with each other. Cu, Ni and Ti can form a eutectic structure, effectively reducing the melting point of Ti alloy, and can also improve the fluidity of molten Ti-based solder, improve the filling ability, and facilitate brazing.
[0012] Cr: Cr can improve the corrosion resistance of the solder, especially in an environment containing corrosive media. The protective film formed by Cr in the solder can prevent the corrosive media from corroding the weld and extend the service life of the weld.
[0013] The second technical solution adopted by the present invention is: a method for preparing a Ti-based flux-cored wire suitable for laser brazing of titanium alloy thin plates, and the specific operating steps are as follows: Step 1: First, clean the TA1 tape with a mixture of acetone and NaOH, then rinse with clean water, and finally ultrasonically clean with ethanol to obtain a clean TA1 tape; Step 2: Prepare the wire core according to the atomic percentage, the core includes Zr: 20%~45%, Cu: 20%, Ni: 20%, Cr: 15%~40% according to the atomic percentage, convert the atomic percentage into mass percentage, and then weigh each raw material powder according to the mass percentage; Step 3: Mix and dry the raw material powders prepared in step 2, and then put the dried raw material powders into a mixer for dry mixing. When the powders are fully mixed, the core powder is obtained; Step 4: The uniformly mixed flux core powder obtained in step 3 is wrapped in a TA1 belt by a flux cored welding wire making machine, and the TA1 belt is closed by a forming machine to obtain a semi-finished wire with a diameter of 2.1 mm; Step 5: The semi-finished wire with a diameter of 2.1 mm obtained in step 4 is subjected to multiple cold drawing and diameter reduction drawing dies to obtain a Ti-based flux-cored wire brazing material with a diameter of 1.18 mm; Step 6: Wipe the oil stains on the wire solder with a cotton cloth dipped in anhydrous ethanol, and finally straighten the wire through a wire drawing machine, coil it into a disc, and seal it for packaging.
[0014] The present invention is also characterized in that: In step 1, the mass fraction of NaOH in the mixed solution of NaOH and acetone used is 25%, and the mass fraction of acetone is 75%; the ultrasonic cleaning in step 1 is performed for 2 to 3 minutes at a frequency of 25 to 30 kHz.
[0015] In step 2, the particle size of each raw material powder is not greater than 200 μm; The drying temperature in step 3 is 15° C. and the drying time is 30 min.
[0016] In step 5, the specific process of the multi-pass cold drawing and reducing wire drawing die is: passing through the wire drawing dies with diameters of 1.9 mm, 1.7 mm, 1.5 mm, and 1.42 mm in sequence.
[0017] The third technical solution adopted by the present invention is: application of Ti-based cored wire, and the specific operation steps are as follows: The assembled TC4 titanium alloy to be welded is firmly assembled with a fixture, and the Ti-based flux-cored wire brazing material is placed on the weld to be welded. The laser power is set to 600W, and the laser energy density range is 100~200J / mm 3 The scanning speed was 450 mm / s, argon gas was continuously introduced during the laser brazing process, and laser brazing was completed in an argon environment with a gas flow rate of 10 L / min.
[0018] The beneficial effects of the present invention are: (1) When the Ti-based flux-cored wire brazing filler metal designed in the present invention is used for laser brazing of titanium alloy thin plates, the weldability is good, and the obtained brazed joint has a beautiful appearance and is free of welding defects such as pores, inclusions, oxidation, and cracks; and it has high strength and is suitable for welding structures that bear a certain load.
[0019] (2) The Ti-based flux-cored wire brazing filler metal designed in the present invention is used for laser brazing of titanium alloy thin plates. The obtained weld joint has uniform hardness distribution, and the brazed sample has excellent shear tensile properties and corrosion resistance.
[0020] (3) The Ti-based flux-cored wire brazing material designed by the present invention is highly economical, has low requirements on equipment, can achieve simple process and good operability, and is suitable for mass production. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a high-magnification metallographic microstructure image of the TC4 brazed joint prepared in Example 4 of the present invention.
[0022] Figure 2 This is a low-magnification metallographic microstructure image of the TC4 brazed joint prepared in Example 4 of the present invention.
[0023] Figure 3 This is a graph of tensile strength and shear strength of the brazed joints as the Zr element in the brazing paste changes in Examples 1 to 6 of the present invention. DETAILED DESCRIPTION
[0024] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0025] The invention is suitable for Ti-based flux-cored wire for laser brazing of titanium alloy thin plates, the wire comprising a flux core and a sheath, wherein the flux core comprises Zr: 20%-45%, Cu: 20%, Ni: 20%, Cr: 15%-40% by atomic percentage; the sum of the above atomic percentages is 100%, the weld skin is a TA1 strip; the weld skin comprises H: 0.015%, O: 0.18%, N: 0.05%, C: 0.26%, Fe: 0.2%, and the balance is Ti by mass percentage.
[0026] Example 1 The present invention also provides a method for preparing a Ti-based flux-cored wire brazing material for laser brazing of titanium alloy thin plates, the specific steps of which are as follows: Step 1: First, clean the TA1 tape with a mixture of acetone and NaOH, then rinse with clean water, and finally ultrasonically clean with ethanol to obtain a clean TA1 tape; Step 2: Prepare the wire core according to the atomic percentage, the total atomic percentage is 100%, including Zr: 20%, Cu: 20%, Ni: 20%, Cr: 40%. Convert the atomic percentage into mass percentage Zr: 28.74%, Cu: 20.01%, Ni: 18.48%, Cr: 32.77%. Then weigh each raw material powder according to the mass percentage; Step 3: Dry the mixed powder prepared in step 2 at a drying temperature of 15°C for 30 minutes, and then put the dried raw material powder into a mixer for dry mixing. When the powder is fully mixed, the core powder is obtained; Step 4: The uniformly mixed flux core powder obtained in step 3 is wrapped in a TA1 belt by a flux cored welding wire making machine, and the TA1 belt is closed by a forming machine to obtain a semi-finished wire with a diameter of 2.1 mm; Step 5: The flux-cored wire solder precursor with a diameter of 2.1 mm obtained in step 4 is subjected to multiple cold drawing and diameter reduction drawing dies to obtain a wire solder with a diameter of 1.18 mm; Step 6: Wipe the oil stains on the welding wire with a cotton cloth dipped in anhydrous ethanol. Finally, the wire is straightened by a wire drawing machine, coiled into a disc, and sealed for packaging.
[0027] The laser brazing process of TC4 titanium alloy in Example 1 is as follows: the assembled TC4 titanium alloy to be welded is firmly assembled with a fixture, the Ti-based flux-cored wire brazing material prepared in step 6 is placed on the weld to be welded, the laser power is set to 600W, and the laser energy density range is 100~200J / mm 3 The scanning speed is 450mm / s. Argon gas is continuously introduced during the laser brazing process to prevent oxidation during the welding process. Laser brazing is completed in an argon gas environment with a gas flow rate of 5~10L / min. The Ti-based flux-cored wire brazing filler metal is used to braze TC4 titanium alloy. The weld is beautifully formed without defects such as pores, inclusions, cracks, and oxidation. The maximum hardness of the brazed joint can reach 400HV in the performance test. 0.5 The tensile strength is 190MPa, the shear strength is 340MPa, and all the properties are excellent, meeting the use requirements.
[0028] Example 2 The present invention provides a method for preparing a Ti-based flux-cored wire brazing material for laser brazing of titanium alloy thin plates, and the specific steps are as follows: Step 1: First, clean the TA1 tape with a mixture of acetone and NaOH, then rinse with clean water, and finally ultrasonically clean with ethanol to obtain a clean TA1 tape; Step 2: Prepare the wire core according to the atomic percentage, the total atomic percentage is 100%, including Zr: 25%, Cu: 20%, Ni: 20%, Cr: 35%. Convert the atomic percentage into mass percentage Zr: 34.85%, Cu: 19.42%, Ni: 17.93%, Cr: 27.80%, and then weigh each raw material powder according to the mass percentage; Step 3: Dry the mixed powder prepared in step 2 at a drying temperature of 15°C for 30 minutes, and then put the dried raw material powder into a mixer for dry mixing. When the powder is fully mixed, the core powder is obtained; Step 4: The uniformly mixed flux core powder obtained in step 3 is wrapped in a TA1 belt by a flux cored welding wire making machine, and the TA1 belt is closed by a forming machine to obtain a semi-finished wire with a diameter of 2.1 mm; Step 5: The flux-cored wire solder precursor with a diameter of 2.1 mm obtained in step 4 is subjected to multiple cold drawing and diameter reduction drawing dies to obtain a wire solder with a diameter of 1.18 mm; Step 6: Wipe the oil stains on the welding wire with a cotton cloth dipped in anhydrous ethanol. Finally, the wire is straightened by a wire drawing machine, coiled into a disc, and sealed for packaging.
[0029] The laser brazing process of TC4 titanium alloy in Example 2 is as follows: the assembled TC4 titanium alloy to be welded is firmly assembled with a fixture, the Ti-based flux-cored wire brazing material prepared in step 6 is placed on the weld to be welded, the laser power is set to 600W, and the laser energy density range is 100~200J / mm 3 The scanning speed is 450mm / s. Argon gas is continuously introduced during the laser brazing process to prevent oxidation during the welding process. Laser brazing is completed in an argon gas environment with a gas flow rate of 5~10L / min. The Ti-based flux-cored wire brazing filler metal is used to braze TC4 titanium alloy. The weld is beautifully formed without defects such as pores, inclusions, cracks, and oxidation. The maximum hardness of the brazed joint can reach 423HV in the performance test. 0.5 The tensile strength is 206MPa and the shear strength is 374MPa. All the properties are excellent and meet the use requirements.
[0030] Example 3 Step 1: First, clean the TA1 tape with a mixture of acetone and NaOH, then rinse with clean water, and finally ultrasonically clean with ethanol to obtain a clean TA1 tape; In step 1, the mass fraction of NaOH in the mixed solution of NaOH and acetone is 25%, and the mass fraction of acetone is 75%. Ultrasonic cleaning is performed for 2-3 minutes at a frequency of 25-30 kHz.
[0031] Step 2: Prepare the wire core according to the atomic percentage, the total atomic percentage is 100%, including Zr: 30%, Cu: 20%, Ni: 20%, Cr: 20%. Convert the atomic percentage into mass percentage Zr: 43.98%, Cu: 20.43%, Ni: 18.87%, Cr: 16.72%, and then weigh each raw material powder according to the mass percentage; In step 2, the particle size of each raw material powder is not greater than 200 μm.
[0032] Step 3: Dry the mixed powder prepared in step 2 at a drying temperature of 15°C for 30 minutes, and then put the dried raw material powder into a mixer for dry mixing. When the powder is fully mixed, the core powder is obtained; Step 4: The uniformly mixed flux core powder obtained in step 3 is wrapped in a TA1 belt by a flux cored welding wire making machine, and the TA1 belt is closed by a forming machine to obtain a semi-finished wire with a diameter of 2.1 mm; Step 5: The flux-cored wire solder precursor with a diameter of 2.1 mm obtained in step 4 is subjected to multiple cold drawing and diameter reduction drawing dies to obtain a wire solder with a diameter of 1.18 mm; In step 5, the specific process of the multi-pass cold drawing and reducing wire drawing die is: passing through the wire drawing dies with diameters of 1.9 mm, 1.7 mm, 1.5 mm, and 1.42 mm in sequence.
[0033] Step 6: Wipe the oil stains on the welding wire with a cotton cloth dipped in anhydrous ethanol. Finally, the wire is straightened by a wire drawing machine, coiled into a disc, and sealed for packaging.
[0034] The laser brazing process of TC4 titanium alloy in Example 3 is as follows: the assembled TC4 titanium alloy to be welded is firmly assembled with a fixture, the Ti-based flux-cored wire brazing material prepared in step 6 is placed on the weld to be welded, the laser power is set to 600W, and the laser energy density range is 100~200J / mm 3 The scanning speed is 450mm / s. Argon gas is continuously introduced during the laser brazing process to prevent oxidation during the welding process. Laser brazing is completed in an argon gas environment with a gas flow rate of 10L / min. The Ti-based flux-cored wire brazing filler metal is used to braze TC4 titanium alloy. The weld is beautifully formed without defects such as pores, inclusions, cracks, and oxidation. The maximum hardness of the brazed joint can reach 452HV in the performance test. 0.5 The tensile strength is 246MPa, the shear strength is 429MPa, and all the properties are excellent, meeting the use requirements.
[0035] Example 4 Step 1: First, clean the TA1 tape with a mixture of acetone and NaOH, then rinse with clean water, and finally ultrasonically clean with ethanol to obtain a clean TA1 tape; In step 1, the mass fraction of NaOH in the mixed solution of NaOH and acetone is 25%, and the mass fraction of acetone is 75%. Ultrasonic cleaning is performed for 2-3 minutes at a frequency of 25-30 kHz.
[0036] Step 2: Prepare the wire core according to the atomic percentage, the total atomic percentage is 100%, including Zr: 35%, Cu: 20%, Ni: 20%, Cr: 20%. Convert the atomic percentage into mass percentage Zr: 47.82%, Cu: 19.03%, Ni: 17.57%, Cr: 15.58%, and then weigh each raw material powder according to the mass percentage; In step 2, the particle size of each raw material powder is not greater than 200 μm.
[0037] Step 3: Dry the mixed powder prepared in step 2 at a drying temperature of 15°C for 30 minutes, and then put the dried raw material powder into a mixer for dry mixing. When the powder is fully mixed, the core powder is obtained; Step 4: The uniformly mixed flux core powder obtained in step 3 is wrapped in a TA1 belt by a flux cored welding wire making machine, and the TA1 belt is closed by a forming machine to obtain a semi-finished wire with a diameter of 2.1 mm; Step 5: The flux-cored wire solder precursor with a diameter of 2.1 mm obtained in step 4 is subjected to multiple cold drawing and diameter reduction drawing dies to obtain a wire solder with a diameter of 1.18 mm; In step 5, the specific process of the multi-pass cold drawing and reducing wire drawing die is: passing through the wire drawing dies with diameters of 1.9 mm, 1.7 mm, 1.5 mm, and 1.42 mm in sequence.
[0038] Step 6: Wipe the oil stains on the welding wire with a cotton cloth dipped in anhydrous ethanol. Finally, the wire is straightened by a wire drawing machine, coiled into a disc, and sealed for packaging.
[0039] The laser brazing process of TC4 titanium alloy in Example 4 is as follows: the assembled TC4 titanium alloy to be welded is firmly assembled with a fixture, the Ti-based flux-cored wire brazing material prepared in step 6 is placed on the weld to be welded, the laser power is set to 600W, and the laser energy density range is 200J / mm 3 The scanning speed was 450 mm / s. Argon was continuously introduced during the laser brazing process to prevent oxidation during the welding process. Laser brazing was completed in an argon environment with a gas flow rate of 10 L / min. The Ti-based flux-cored wire brazing filler metal was used to braze TC4 titanium alloy. The weld was beautifully formed without defects such as pores, inclusions, cracks, and oxidation. The metallographic structure of the obtained brazed joint was observed (such as Figure 1-2 As shown in the figure, the brazed joint structure consists of a distinct layered structure, which can be divided into three parts: the needle-shaped area, the diffusion reaction area and the central eutectic residual area. The weld and the TC4 matrix are well bonded. The maximum hardness of the brazed joint obtained in the performance test can reach 500HV 0.5 The tensile strength is 310MPa and the shear strength is 485MPa. All the properties are excellent and meet the requirements of use.
[0040] Example 5 Step 1: First, clean the TA1 tape with a mixture of acetone and NaOH, then rinse with clean water, and finally ultrasonically clean with ethanol to obtain a clean TA1 tape; In step 1, the mass fraction of NaOH in the mixed solution of NaOH and acetone is 25%, and the mass fraction of acetone is 75%. Ultrasonic cleaning is performed for 2-3 minutes at a frequency of 25-30 kHz.
[0041] Step 2: Prepare the wire core according to the atomic percentage, the total atomic percentage is 100%, including Zr: 40%, Cu: 20%, Ni: 20%, Cr: 20%. Convert the atomic percentage into mass percentage Zr: 51.16%, Cu: 17.82%, Ni: 16.45%, Cr: 14.58%, and then weigh each raw material powder according to the mass percentage; In step 2, the particle size of each raw material powder is not greater than 200 μm.
[0042] Step 3: Dry the mixed powder prepared in step 2 at a drying temperature of 15°C for 30 minutes, and then put the dried raw material powder into a mixer for dry mixing. When the powder is fully mixed, the core powder is obtained; Step 4: The uniformly mixed flux core powder obtained in step 3 is wrapped in a TA1 belt by a flux cored welding wire making machine, and the TA1 belt is closed by a forming machine to obtain a semi-finished wire with a diameter of 2.1 mm; Step 5: The flux-cored wire solder precursor with a diameter of 2.1 mm obtained in step 4 is subjected to multiple cold drawing and diameter reduction drawing dies to obtain a wire solder with a diameter of 1.18 mm; In step 5, the specific process of the multi-pass cold drawing and reducing wire drawing die is: passing through the wire drawing dies with diameters of 1.9 mm, 1.7 mm, 1.5 mm, and 1.42 mm in sequence.
[0043] Step 6: Wipe the oil stains on the welding wire with a cotton cloth dipped in anhydrous ethanol. Finally, the wire is straightened by a wire drawing machine, coiled into a disc, and sealed for packaging.
[0044] The laser brazing process of TC4 titanium alloy in Example 5 is as follows: the assembled TC4 titanium alloy to be welded is firmly assembled with a fixture, the Ti-based flux-cored wire brazing material prepared in step 6 is placed on the weld to be welded, the laser power is set to 600W, and the laser energy density range is 200J / mm 3 , the scanning speed is 450mm / s, argon is continuously introduced during the laser brazing process to prevent oxidation during the welding process, and the laser brazing is completed in an argon environment with a gas flow rate of 10L / min. The Ti-based flux-cored wire brazing filler metal is used to braze TC4 titanium alloy. The weld is beautifully formed, without defects such as pores, inclusions, cracks, oxidation, etc., and the weld is well bonded to the TC4 matrix. The maximum hardness of the obtained brazed joint can reach 482HV in the performance test. 0.5 The tensile strength is 293MPa, the shear strength is 464MPa, and all the properties are excellent, meeting the use requirements.
[0045] Example 6 Step 1: First, clean the TA1 tape with a mixture of acetone and NaOH, then rinse with clean water, and finally ultrasonically clean with ethanol to obtain a clean TA1 tape; In step 1, the mass fraction of NaOH in the mixed solution of NaOH and acetone is 25%, and the mass fraction of acetone is 75%. Ultrasonic cleaning is performed for 2-3 minutes at a frequency of 25-30 kHz.
[0046] Step 2: Prepare the wire core according to the atomic percentage, the total atomic percentage is 100%, including Zr: 45%, Cu: 20%, Ni: 20%, Cr: 15%. Convert the atomic percentage into mass percentage Zr: 56.00%, Cu: 17.43%, Ni: 15.99%, Cr: 10.67%, and then weigh each raw material powder according to the mass percentage; In step 2, the particle size of each raw material powder is not greater than 200 μm.
[0047] Step 3: Dry the mixed powder prepared in step 2 at a drying temperature of 15°C for 30 minutes, and then put the dried raw material powder into a mixer for dry mixing. When the powder is fully mixed, the core powder is obtained; Step 4: The uniformly mixed flux core powder obtained in step 3 is wrapped in a TA1 belt by a flux cored welding wire making machine, and the TA1 belt is closed by a forming machine to obtain a semi-finished wire with a diameter of 2.1 mm; Step 5: The flux-cored wire solder precursor with a diameter of 2.1 mm obtained in step 4 is subjected to multiple cold drawing and diameter reduction drawing dies to obtain a wire solder with a diameter of 1.18 mm; In step 5, the specific process of the multi-pass cold drawing and reducing wire drawing die is: passing through the wire drawing dies with diameters of 1.9 mm, 1.7 mm, 1.5 mm, and 1.42 mm in sequence.
[0048] Step 6: Wipe the oil stains on the welding wire with a cotton cloth dipped in anhydrous ethanol. Finally, the wire is straightened by a wire drawing machine, coiled into a disc, and sealed for packaging.
[0049] The laser brazing process of TC4 titanium alloy in Example 6 is as follows: the assembled TC4 titanium alloy to be welded is firmly assembled with a fixture, the Ti-based flux-cored wire brazing material prepared in step 6 is placed on the weld to be welded, the laser power is set to 600W, and the laser energy density range is 100J / mm 3 , the scanning speed is 450mm / s, argon is continuously introduced during the laser brazing process to prevent oxidation during the welding process, and the laser brazing is completed in an argon environment with a gas flow rate of 10L / min. The Ti-based flux-cored wire brazing filler metal is used to braze TC4 titanium alloy. The weld is beautifully formed, without defects such as pores, inclusions, cracks, oxidation, etc., and the weld is well bonded to the TC4 matrix. The maximum hardness of the obtained brazed joint can reach 448HV in the performance test. 0.5 The tensile strength is 263MPa, the shear strength is 410MPa, and all the properties are excellent, meeting the use requirements.
Claims
1. Ti-based flux-cored wire suitable for laser brazing of titanium alloy thin plates, characterized in that: The wire material comprises a core and a sheath, wherein the core comprises Zr: 20%-45%, Cu: 20%, Ni: 20%, Cr: 15%-40% in atomic percentage; the sum of the above atomic percentages is 100%, and the welding sheath is a TA1 tape.
2. The Ti-based flux-cored wire suitable for laser brazing of titanium alloy thin plates according to claim 1, characterized in that: The weld skin includes, by mass percentage, H: 0.015%, O: 0.18%, N: 0.05%, C: 0.26%, Fe: 0.2%, and the balance is Ti.
3. A method for preparing a Ti-based flux-cored wire suitable for laser brazing of titanium alloy thin plates, characterized in that: The specific steps are as follows: Step 1: First, clean the TA1 tape with a mixture of acetone and NaOH, then rinse with clean water, and finally ultrasonically clean with ethanol to obtain a clean TA1 tape; Step 2: Prepare the wire core according to the atomic percentage, the core includes Zr: 20%~45%, Cu: 20%, Ni: 20%, Cr: 15%~40% according to the atomic percentage, convert the atomic percentage into mass percentage and weigh each raw material powder; Step 3: Mix the raw material powders prepared in step 2 and dry them, then put the dried raw material powders into a mixer for dry mixing, and wait until the powders are fully mixed to obtain the core powder; Step 4: The uniformly mixed flux core powder obtained in step 3 is wrapped in a TA1 belt by a flux cored welding wire making machine, and the TA1 belt is closed by a forming machine to obtain a semi-finished wire with a diameter of 2.1 mm; Step 5: The semi-finished wire with a diameter of 2.1 mm obtained in step 4 is subjected to multiple cold drawing and diameter reduction drawing dies to obtain a Ti-based flux-cored wire brazing material with a diameter of 1.18 mm; Step 6: Wipe the oil stains on the wire solder with a cotton cloth dipped in anhydrous ethanol, and finally straighten the wire through a wire drawing machine, coil it into a disc, and seal it for packaging.
4. The method for preparing a Ti-based flux-cored wire suitable for laser brazing of titanium alloy thin plates according to claim 3, characterized in that: In step 1, the mass fraction of NaOH in the mixed solution of NaOH and acetone used is 25%, and the mass fraction of acetone is 75%; the ultrasonic cleaning in step 1 is performed for 2 to 3 minutes at a frequency of 25 to 30 kHz.
5. The method for preparing Ti-based flux-cored wire suitable for laser brazing of titanium alloy thin plates according to claim 3, characterized in that: In step 2, the particle size of each raw material powder is not greater than 200 μm.
6. The method for preparing Ti-based flux-cored wire suitable for laser brazing of titanium alloy thin plates according to claim 3, characterized in that: The drying temperature in step 3 is 15° C. and the drying time is 30 min.
7. The method for preparing Ti-based flux-cored wire suitable for laser brazing of titanium alloy thin plates according to claim 3, characterized in that: In step 5, the specific process of the multi-pass cold drawing and reducing wire drawing die is: passing through the wire drawing dies with diameters of 1.9 mm, 1.7 mm, 1.5 mm, and 1.42 mm in sequence.
8. Application of Ti-based cored wire, characterized in that: It is suitable for laser brazing of titanium alloy thin plates. The specific operation steps are as follows: firmly assemble the assembled TC4 titanium alloy to be welded with a fixture, place the Ti-based flux-cored wire brazing material on the weld to be welded, set the laser power to 600W, and the laser energy density range is 100~200J / mm 3 The scanning speed was 450 mm / s, argon gas was continuously introduced during the laser brazing process, and laser brazing was completed in an argon environment with a gas flow rate of 10 L / min.
Citation Information
Patent Citations
Nickel-saving high-nitrogen austenitic stainless steel gas-shielded flux-cored wire and preparation method thereof
CN113146097A
Gas-shielded flux-cored wire for TC32 titanium alloy welding and preparation method of gas-shielded flux-cored wire
CN117260057A
System for managing creation cost of brand
KR1020240093399A
Brazing material with continuous length layer of elastomer containing a flux
SG142519A1